Atmospheric Modeling: A Comprehensive Review of Numerical Approaches and Applications - Aaysha Gupta1 (International Journal of Atmosphere, 2024)
Atmospheric modeling plays a crucial role in understanding and predicting atmospheric processes, weather patterns, and climate variability. This review synthesizes current methodologies and applications across several types of atmospheric models, including numerical weather prediction (NWP), climate models, air quality models, and chemical transport models. We explore the intricacies of data assimilation, model evaluation, parameterization, and the importance of high-performance computing in advancing model accuracy and efficiency. Special emphasis is placed on sensitivity analysis, model intercomparison, and uncertainty quantification, which are critical for assessing the reliability of model outputs. Additionally, we examine aerosol-cloud interactions and their implications for radiative transfer modeling and climate sensitivity. The integration of hydrological models and regional climate modeling enhances our understanding of localized climatic effects. This manuscript aims to provide a comprehensive overview of atmospheric modeling, emphasizing its significance in developing climate scenarios and informing policy decisions related to climate change and environmental management. By identifying existing gaps in research and potential areas for future study, we hope to contribute to the ongoing discourse in atmospheric science.
Keywords: Aerosol-cloud interactions; Air quality models; Atmospheric modeling; Chemical transport models; Climate models; Data assimilation; High-performance computing; Numerical weather prediction; Sensitivity analysis; Uncertainty quantification